Serum metabolic profiling of patients with diabetic kidney disease based on gas chromatography-mass spectrometry - Bian, Xueyan; Wang, Chenwen; Wang, Majie; Yin, Ailing; Xu, Jiayan; Liu, Mijia; Wang, Hui; Cao, Yating; Huang, Xin; Qin, Chenxue; Zhang, Ye; Yu, Heming (Frontiers in Molecular Biosciences, 2025)
IntroductionGiven the increasing incidence rate of diabetic kidney disease (DKD), there is an urgent need for methods to diagnose and treat DKD in clinics.MethodsSerum samples were collected from 56 DKD patients and 32 healthy controls (HCs) at the First Affiliated Hospital of Ningbo University, and the metabolic profiles were obtained through untargeted metabolomics using gas chromatography mass spectrometry. The data were then analyzed using principal components analysis, orthogonal partial least-squares discriminant analysis, Pearson correlation analysis, and receiver operating characteristic (ROC) curve.ResultsIt was found that the serum metabolic profiles of the DKD patients were significantly different from those of the HCs. A total of 68 potential differential metabolites were identified that were involved in arginine biosynthesis, ascorbate and aldarate metabolism, and galactose metabolism, among others; a total of 31 differential metabolites were also identified between early-stage (EDG) and late-stage (LDG) DKD patients. Additionally, 30 significant metabolic differences were observed among the EDG, LDG, and HC groups. Based on Pearson correlation analysis between the abundances of the differential metabolites and clinical markers (estimated glomerular filtration rate, blood urea nitrogen, serum creatinine, and urinary albumin/creatinine ratio) and area under the ROC curve (AUROC) analysis, the AUROC values of myoinositol and gluconic acid were found to be 0.992 and 0.991, respectively, which can be used to distinguish DKD patients from HCs.DiscussionThese results indicate that myoinositol and gluconic acid could possibly be used as biomarkers of DKD.